The effect of prasugrel on ADP-stimulated markers of platelet activation in patients with sickle cell disease - Jakubowski, Joseph A.; Zhou, Chunmei; Winters, Kenneth J.; Lachno, D. Richard; Howard, Jo; Payne, Christopher D.; Mant, Timothy; Jurcevic, Stipo; Frelinger, Andrew L. (Platelets (Edinburgh), 2015)
Abstract Platelets of patients with sickle cell disease (SCD) show evidence of mild activation in the non-crisis steady state and greater activation during vaso-occlusive crises (VOC). Prasugrel, a potent inhibitor of ADP-mediated platelet activation and aggregation, may be useful in attenuating VOC. We compared platelet responses to ADP stimulation in patients with SCD and healthy subjects before and after treatment with prasugrel. In a phase 1 study, platelet biomarker levels were assessed in 12 adult patients with SCD and 13 healthy subjects before and after 12 ± 2 days of 5.0 or 7.5 mg/day prasugrel. The following were determined in whole blood samples stimulated with 20 µM ADP: (i) percentages of monocytes and neutrophils with adherent platelets (cell-platelet aggregates); (ii) the relative number (mass) of platelets associated with each monocyte and neutrophil as reported by CD61 mean fluorescence intensity (MFI) of the monocyte-platelet and neutrophil-platelet aggregates; (iii) the percentages of platelets positive for surface expression of CD40 ligand (CD40L), P-selectin (CD62p) and activated glycoprotein IIb-IIIa (GPIIb-IIIa); and (iv) the percentages of platelets and monocyte-platelet aggregates positive for surface tissue factor (TF) expression. At baseline, there were no significant differences between cohorts in the percentages of platelets expressing activation biomarkers. Following 12 days of prasugrel administration, the percentages of platelets expressing activation biomarkers following ADP stimulation were reduced in both cohorts, and there were no significant differences between groups. Both patients with SCD and healthy subjects had significant reductions in the monocyte-platelet and neutrophil-platelet aggregate MFI and the percentage of platelets expressing P-selectin and activated GPIIb-IIIa (all p < 0.05). Healthy subjects also had significant reductions in monocyte-platelet aggregate percentages (p = 0.004), neutrophil-platelet aggregate percentages (p = 0.011) and the percentage of CD40L-positive platelets (p = 0.044) that were not observed in patients with SCD. Prasugrel administration to SCD patients attenuates ex vivo ADP-stimulated platelet activation as measured by the percentage of platelets positive for P-selectin and GPIIb-IIIa, thus reducing the proportion of platelets that may participate in aggregates. Furthermore, prasugrel decreases ex vivo ADP-stimulated platelet aggregation with monocytes and neutrophils as measured by the monocyte-platelet and neutrophil-platelet aggregate MFI. This implies that in the presence of prasugrel, fewer platelets adhere to monocytes and neutrophils, which may result in reducing cell-platelet aggregate size. Therefore, reduced platelet reactivity and decreased size of leukocyte-platelet aggregates suggest additional mechanisms by which prasugrel may provide benefit to patients with SCD and support further investigation of possible therapeutic benefits of prasugrel in this population.